Psychological and Social Adjustment among Autistic Children:Afield Studying in Autism Centers in the City of Sulaymaniyah - Muhammad Rashid, Sherine Ibrahim (Journal of Tikrit University for Humanities, 2024)
The aim of this study is to determine the level of psychological and social adjustment of parents of children with autism, and knowing the statistical differences in psychological adjustment and social adjustment according to the categories gender, place of residence, education level, economic level, child number, gender of autistic child, number of autistic children. The research consists of three parts. The first part is the framework of the research that includes three topics. The second part of the study deals with the square Practical Psychological Adjustment and Autism. The third part is consisted of field research, which is consisted of three topics. The research community is consisted of parents of children with autism in autism centers. The number of which were (444) parents, the sample of the study was (146) parents. The most important tools received were psychological rehabilitation and parental support Children with autism. The study reached to several conclusions. The most important of which are: Very low level of mental adjustment in parents of children with autism. 2- High level of social adaptation of parents of children with autism. 3- High level of knowledge of parents of children with autism. 4- There is a direct relationship between mental adaptation and community. 4- Lack of statistical differences between mental and social adjustment according to the factors (gender, place of residence, education level, economic level, number of children, Gender of children with autism, number of children with autism).